A class of time‐fractional reaction‐diffusion equation with nonlocal boundary condition. (12th February 2018) - Zhou, Yong; Shangerganesh, L.; Manimaran, J.; Debbouche, Amar
Abstract : The purpose of the study is to analyze the time‐fractional reaction‐diffusion equation with nonlocal boundary condition. The proposed model is used to predict the invasion of tumor and its growth. Further, we establish the existence and uniqueness of a weak solution of the proposed model using the Faedo‐Galerkin method and compactness arguments.